Community interventions and strategies for caries control in Latin American and Caribbean countries - Antônio Pedro RICOMINI FILHO; Bertha Angélica CHÁVEZ; Rodrigo Andrés GIACAMAN; Paulo FRAZÃO; Jaime Aparecido CURY (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Dental caries remains highly prevalent in Latin American and Caribbean countries (LACC). However, this disease can be controlled through interventions that implement evidence-based strategies in an affordable manner and that target all population groups instead of the most affluent only. Therefore, the aim of this report was to summarize the main scientifically documented community interventions and strategies based on restriction of sugars consumption, use of fluoride, and the use of occlusal sealants for caries control in LACC. A critical literature review was carried out in a systematic manner that included defined search strategies, independent review of the identified publications, and compilation of results in this report. Three systematic searches were conducted using the PubMed, LILACS, and SciELO databases to identify studies related to community interventions and strategies for caries control in LACC. Of the 37 publications identified, twenty-six focused on fluoride use, eight on occlusal sealant use, and three on the restriction of sugar consumption. Documented community interventions for sugars restriction were scarce in the region and were based on food supplementation, sugar replacement, and education. Thus, local and/or national policies should prioritize investment in upstream, coherent, and integrated population-wide policies such as taxes on sugary drinks and stronger regulation of advertising and promotion of sugary foods and drinks mainly targeting children. The main fluoride-based strategies used drinking water, refined domestic salt, cow milk, toothpaste and, to a lesser extent, mouth-rinses, acidulated phosphate fluoride (APF) gels, and varnishes to deliver fluoride to the population. Evidence of fluoride use was seen in Argentina, Belize, Bolivia, Brazil, Chile, Colombia, Costa Rica, Cuba, Dominican Republic, Ecuador, El Salvador, Guatemala, Haiti, Honduras, Mexico, Nicaragua, Panama, Paraguay, Peru, Uruguay, and Venezuela. Studies reporting the use of occlusal sealants were mainly located in Brazil, Chile, Colombia, Costa Rica, Peru, Mexico, and Venezuela. Community interventions restricting sugar consumption should be implemented at the individual level and through public policies. The use of fluoride must be monitored at the local, regional, and national levels so as to achieve maximum anti-caries effect while also minimizing the risk of dental fluorosis. Moreover, fluoridated water and salt programs, used as a mutually exclusive community level strategy for caries control, should expand their benefits to reach non-covered areas of the LACC while also simultaneously providing adequate surveillance of the fluoride concentration delivered to the population. Regulating the concentration of soluble fluoride (for anti-caries effect) in dentifrice formulations is also necessary in order to provide the population with an effective strategy for disease control. Targeting culturally appropriate, economically sustainable caries control interventions to rural populations and native ethnic groups such as indigenous people, quilombolas (African-origin), and riverside Amazonian people remains a crucial challenge.